Inclusion Strategies That Work for Adolescent Learners! - Karten, Toby J. (SAGE Publications, 2009)
Strategies to achieve winning results in the inclusive secondary classroom! Backed by the author's three decades of experience, this reader-friendly guidebook provides teachers with a practical approach for creating a successful inclusive secondary classroom. Toby J. Karten helps teachers use a variety of strategies, including differentiated instruction, universal design for learning, brain-based learning, RTI, and evidence-based practice. With helpful forms, activities, graphic organizers, and quotations throughout, this resource: Outlines the theoretical background for creating an incl.